JURASSIC RADIOLARIAN BIOSTRATIGRAPHY OF THE SEDIMENTARY COVER OF OPHIOLITES IN THE MIRDITA AREA, ALBANIA: NEW DATA - Prela, Mensi; Chiari, Marco; Marcucci, Marta (Ofioliti, 2000)
Radiolarian assemblages of Jurassic age were determined in six sections sampled of Kalur Cherts (siliceous sediments on the top of the Mirdita ophiolites) in the Mirdita area (Northern Albania). The studied sections are: Kalur, Lumthi, Bukemira, Stalosi, Simoni and Perlati i Eperm. The radiolarian assemblages indicate that the age of the bottom of the section ranges from late Bajocian-early Bathonian to late Bathonian-early Callovian. These ages are compared with those of other sections of the Kalur Cherts in Northern Albania.